Incentives to literary achievement - Pugh, Berton Homer. (My University, 1892)
Introduction: Few things are more difficult to attain and few things give fuller satisfaction than success in literature. The artist may sit before his canvas for years with the most earnest application and in the end be able to produce a fascinating array of colors in combination, but sometime he will arrive at the point where the combinations end and his skill will have reached its zenith. The actor will practice and perform for weeks and months and as a result become proficient even to popularity, but there is a place where suppleness of muscle and grace of manner no longer improve and the actor has reached his highest plane. But the man who craves wisdom and longs to draw to his fill from the universe of knowledge about him, finds all things different. He may become proficient in one branch of learning but immediately another field is open to him, and so step by step his mind grows on all sides until he becomes a balanced, educated man. Truly the artist, the actor, and the sculptor are men the world would be at loss to part with for their influence on culture is immeasurable. But each is a rock with one side polished, a comet with one gem inlaid; they have sculptured away the undeveloped portion of their minds to leave a moment of their fret profession.
Citation: Pugh, Berton Homer. Incentives to literary achievement. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Incentive; Literary achievement; Artist; Literature; Theses; Manuscripts (documents)